Does Echinoderm research deserve an ethical consideration? - Rubilar, Tamara; Crespi-Abril, Augusto (Revista de Biología Tropical, 2017)
Traditional ethics reflection centers the discussion in conflicts that affect humans. According to epistemology-based ethics, facts are needed to include other living beings as object of ethical consideration. In this sense, huge efforts have been made to demonstrate that animal suffering is real. However, the ethical reflection only reaches large vertebrates and some species of small ones, excluding invertebrates. However, a different approach (ethic-based epistemology) is equally valid and questions the assumptions of traditional ethics. This new insight does not demand facts to demonstrate that living beings should be considered ethically, since ethics should be first than epistemology (facts). Thus, all living beings should be treated with respect and a relationship based on empathy should be established. In this context, we discuss all the advances made in echinoderm research in the last 3000 years and the different uses humans made of these organisms. Finally we emphasize that, when studying echinoderms, a reflection about our behavior as researchers is necessary, and we encourage the use of ethically responsible research. Rev. Biol. Trop. 65(Suppl. 1): S11-S22. Epub 2017 November 01.